Comparison of the real-time precise orbit determination for LEO between kinematic and reduced-dynamic modes. (January 2022) - Wang, Zhiyu; Li, Zishen; Wang, Liang; Wang, Ningbo; Yang, Yang; Li, Ran; Zhang, Yang; Liu, Ang; Yuan, Hong; Hoque, Mainul
Highlights: The first time compared the performance of the real-time KOD and ROD for LEO satellites. Real-time ROD performs more robust and continuity against the KOD when GPS satellites are less than 6. Real-time ROD can improve the accuracy of LEO POD and reduce the convergence time. Abstract: The real-time high-accuracy orbit and clock of the GNSS (Global Navigation Satellite System) are one of the most essential corrections for the real-time kinematic precise orbit determination (POD) mode and reduced-dynamic POD mode for Low Earth Orbit (LEO) satellites. This work is devoted to initially achieve the real-time POD with the two modes and compare their performance. Numerical results showed that (1) the average accuracy improvement of the real-time reduced-dynamic POD relative to the real-time kinematic POD is about 46% on the condition that the number of observable GPS satellites is less than 6; (2) Comparing with the real-time kinematic POD, the real-time reduced-dynamic orbit determination by applying dynamical constraints can improve the accuracy (maximum 12%) of LEO POD and reduce the convergence time (maximum 20%); (3) in most circumstances, the accuracy of real-time kinematic POD and reduced-dynamic POD for LEO are better than 11 cm and 9 cm, respectively, and the reduced-dynamic POD performs more robust against the kinematic POD.